Catalyst for air cathode, method for preparing the same, air cathode, and metal-air battery
Patent Information
- Application Number
- CN202611264066.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]然而,这些催化材料不仅制备工艺复杂,而且基本都是采用掺杂碳材料负载,例如氮掺杂碳材料负载过渡金属,但是氮掺杂的过程基本都是在高温下进行,通过高温热解实现,能耗较高,同时高温导致氮大部分溢出,产物产率低,不利于工业化应用
基于现有金属空气电池正极所用碳负载非贵金属过渡金属催化剂存在的制备工艺复杂、制备过程能耗高、催化性能不足等问题,本发明的发明人通过对非贵金属ORR催化剂例如碳负载非贵金属过渡金属及其制备工艺进行深入研究,突破本领域技术人员的普遍认知,创新地在碳负载非贵金属过渡金属的催化剂中,尽可能使氮以非掺杂在碳晶格中的方式负载,也即不同于普遍的氮掺杂碳结构,主要构建过渡金属-氮配位结构、氮缺陷相关结构为主体的活性位点体系,以及过渡金属氧化物结构共同调控ORR活性,不仅使得制备的ORR催化剂具备较优异的ORR催化活性,而且还能够在相对较低的温度下制备。此外,本发明方法还能够在保证较优异的ORR催化活性的基础上获得催化剂的高产率,有利于降低综合成本,适于工业化应用。
Smart Images

Figure CN123018003A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of air batteries, specifically to a catalyst for an air cathode and its preparation method, an air cathode, and a metal-air battery. Background Technology
[0002] A metal-air battery is a battery system that stores and releases energy through an electrochemical reaction between a metal and oxygen. Its core characteristic is the use of a metal (such as zinc, aluminum, lithium, magnesium, or iron) as the negative electrode and oxygen from the air as the positive electrode active material. Typically, a metal-air battery structure includes a positive electrode (air electrode), a negative electrode (metal electrode), and an electrolyte. The positive electrode (air electrode) generally consists of a catalytic layer, a waterproof and breathable layer, and a metal current-collecting conductive mesh to increase the electrode's mechanical strength. During discharge, oxygen is electrochemically catalytically reduced to hydroxide ions at the three-phase interface, resulting in the reaction: O₂ + 2H₂O + 4e⁻. - →4OH - The theoretical energy density of a metal-air battery is primarily determined by the negative electrode material. This is because the negative electrode stores the main active material inside the battery and can release electrons through oxidation reactions, while oxygen from the air serves as the positive electrode active material, continuously supplied by the external environment. Metal-air batteries possess advantages such as high theoretical capacity, abundant raw materials, relatively low cost, non-toxicity, and environmental friendliness, making them a relatively clean and green energy source.
[0003] In the discharge process of metal-air batteries, the oxygen reduction reaction (ORR) is a key cathode reaction involving complex multi-electron transfer processes, typically accompanied by high overpotentials and slow kinetics, thus limiting the overall energy efficiency and power output of the battery. Currently, although commercial Pt / C catalysts have high ORR activity, they suffer from high cost, resource scarcity, and susceptibility to poisoning and deactivation during long-term operation, making it difficult to meet the needs of large-scale energy storage applications.
[0004] Therefore, non-precious metal ORR catalysts with low cost advantages have become a research focus in this field. For example, nitrogen-doped carbon materials, due to the introduction of nitrogen atoms, can regulate the electronic structure of the carbon framework, increase defect sites, and provide metal coordination sites, which can effectively improve the adsorption and activation ability of carbon materials for oxygen molecules. At the same time, it also promotes the dispersion and stability of transition metal elements such as Fe, Co, and Ni. Therefore, in non-precious metal oxygen reduction catalyst systems, nitrogen-doped carbon materials are often used as important catalyst supports or catalyst hosts to construct highly active and stable MNC (M=Fe, Co, Ni, etc.) catalytic systems. For example, CN119890554A discloses a nitrogen-doped graphene-supported nickel-cobalt diatom catalyst, the preparation method of which includes: S1, mixing nickel salt and cobalt salt with water respectively, and mixing them according to the volume ratio of nickel salt solution to cobalt salt solution of 1:(1~4) to obtain a mixed salt solution; S2, adding the mixed salt solution and deionized water to an ultrasonically treated graphene oxide aqueous solution, stirring and mixing to obtain a precursor solution, wherein the total volume ratio of the mixed salt solution and deionized water to the volume ratio of the graphene oxide aqueous solution is 3:(3~5); S3, transferring the precursor solution to a hydrothermal reactor for hydrothermal reaction to obtain a precursor gel; S4, freeze-drying the precursor gel; S5, thermally reducing the freeze-dried precursor under an ammonia atmosphere to obtain a nitrogen-doped graphene-supported nickel-cobalt diatom catalyst.
[0005] For example, CN106887576B discloses a nano-nickel-iron nitride composite material supported on a cobalt-nitrogen co-doped carbon material. This composite material uses a cobalt-nitrogen co-doped carbon material as a carrier; nickel-iron nitride nanoparticles are in-situ loaded on the surface of the cobalt-nitrogen co-doped carbon material; the size of the nickel-iron nitride nanoparticles is 10–50 nm; the mass percentage of nickel-iron nitride nanoparticles in the composite material is 33.3–55.6 wt%; the composite material is prepared by the following process: 1) After ultrasonically dispersing the cobalt-nitrogen co-doped carbon material in an organic solvent, adding a mixture containing Ni(NO3)2·6H2O, F… A mixed solution of e(NO3)3·9H2O and urea was stirred, reacted, washed, centrifuged, and dried to obtain a nano-nickel-iron hydrotalcite composite material supported on a cobalt-nitrogen co-doped carbon material carrier; 2) The material obtained in step 1) was calcined in an ammonia atmosphere to obtain a nano-nickel-iron nitride composite material supported on a cobalt-nitrogen co-doped nitrogen-carbon material carrier; The molar ratio of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and urea in the mixed solution in step 1) was 1.25~1.3∶0.42∶150, and the volume ratio of the mixed solution to the organic solvent was 2.5~3∶1.
[0006] For example, CN110247068B discloses an iron / copper nitrogen-doped graphene zinc-air battery cathode catalyst (i.e., air cathode catalyst), and CN114744224B discloses a nitrogen-doped carbon nanotube-supported nickel-cobalt composite nanowire.
[0007] However, these catalytic materials are not only complex to prepare, but they are also basically supported by doped carbon materials, such as nitrogen-doped carbon materials supporting transition metals. However, the nitrogen doping process is basically carried out at high temperature through high-temperature pyrolysis, which consumes a lot of energy. At the same time, the high temperature causes most of the nitrogen to escape, resulting in low product yield, which is not conducive to industrial application.
[0008] It should be noted that the information disclosed in the background section above is only for understanding the background of this application. Therefore, the background section of this invention may include background information about the problems or environment of this invention, and is not necessarily a description of the prior art. Thus, the content included in the background section does not constitute an admission of the prior art by the applicant. Summary of the Invention
[0009] The purpose of this invention is to overcome one or more shortcomings in the prior art and provide a new catalyst for air cathode and its preparation method.
[0010] The present invention also provides an air cathode comprising the above-mentioned novel air cathode catalyst and a metal-air battery.
[0011] To achieve the above objectives, the present invention employs the following technical solution: A catalyst for an air cathode, the catalyst comprising conductive carbon, a transition metal, and nitrogen; a portion of the nitrogen exists in the form of a metal-nitrogen coordination structure with the transition metal, wherein at least a portion of the metal-nitrogen coordination structure contains a transition metal center with an actual coordination number less than the theoretical coordination number, and a portion of the nitrogen exists in the form of a carbon-nitrogen compound, wherein the transition metal also exists in the form of a transition metal oxide.
[0012] In this invention, the actual coordination number of the transition metal center is less than the theoretical coordination number. The state represented by the metal nitrogen coordination structure is that the actual coordination number of the transition metal center is lower than the theoretical maximum coordination number under this oxidation state and ligand field, resulting in empty coordination sites around the metal, that is, exhibiting unsaturated coordination characteristics.
[0013] In some embodiments of the present invention, the transition metal includes at least cobalt, and the metal nitrogen coordination structure includes CoN. 4-x x is greater than or equal to 0 and less than 4.
[0014] According to certain aspects of the present invention, x can be 0, 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92 0.95, 0.98, 1.0, 1.01, 1.02, 1.05, 1.08, 1.1, 1.12, 1.15, 1.18, 1.2, 1.22, 1.25, 1.28, 1.30, 1.32, 1.35, 1.38, 1.40, 1.42, 1.45, 1.48, 1.50, 1.52, 1.55, 1.58, 1.60, 1.62, 1.65, 1.68, 1.7, 1.72, 1.75, 1.78, 1.8, 1.82, 1.85, 1.88, 1.9, 1.92, 1.9 5, 1.98, 2.0, 2.01, 2.02, 2.05, 2.08, 2.1, 2.12, 2.15, 2.18, 2.2, 2.22, 2.25, 2.28, 2.30, 2.32, 2.35, 2.38, 2.40, 2.42, 2.45, 2.48, 2.50, 2.52, 2.55, 2.58, 2.60, 2.62, 2.65, 2.68, 2.7, 2.72, 2.75, 2.78, 2.8, 2.82, 2.85, 2.88, 2.9, 2.92, 2.95, 2. 98, 3.0, 3.01, 3.02, 3.05, 3.08, 3.1, 3.12, 3.15, 3.18, 3.2, 3.22, 3.25, 3.28, 3.30, 3.32, 3.35, 3.38, 3.40, 3.42, 3.45, 3.48, 3.50, 3.52, 3.55, 3.58, 3.60, 3.62, 3.65, 3.68, 3.7, 3.72, 3.75, 3.78, 3.8, 3.82, 3.85, 3.88, 3.9, 3.92, 3.95, 3.98, etc.
[0015] In some embodiments of the present invention, the transition metal includes cobalt and nickel, wherein the molar ratio of cobalt to nickel is 1:0-5.0, more specifically 1:0.1-2.0, and even more specifically 1:0.5-1.5.
[0016] According to some specific aspects of the present invention, the molar ratio of cobalt to nickel is 1:0, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, etc.
[0017] In the catalyst system of the present invention, cobalt is preferably used as the main transition metal catalytic site, and nickel is more preferably used in combination. The role of nickel is not as the main ORR active center, but rather, in an appropriate proportion, it is beneficial to adjust the local electronic environment of the cobalt-related active structure, thereby enhancing the overall ORR catalytic performance.
[0018] In some embodiments of the present invention, the carbon-nitrogen compound includes carbon nitride, and further includes carbon-nitrogen-hydrogen compound.
[0019] According to certain aspects of the present invention, carbon nitride may be C3N4.
[0020] According to some specific aspects of the present invention, the carbon, nitrogen, and hydrogen compounds may be the nitrogen source residue itself during the preparation of the catalyst, or a cracking intermediate, or a nitrogen-containing structure that is not completely condensed, etc.
[0021] In some embodiments of the present invention, the molar ratio of transition metal to nitrogen in the catalyst is 1:5-25, further 1:8-18, and even further 1:10-15.
[0022] In some embodiments of the present invention, when the catalyst is analyzed by Raman scattering spectroscopy using a laser with a wavelength of 532 nm, the Raman shift is 1330-1360 cm⁻¹. -1 The D peak intensity is I D The Raman shift is 1570-1600 cm. -1 The intensity of the G peak is I G 2.5≤I D / I G Furthermore, 2.5≤I D / I G ≤5.0, and further, 2.8≤I D / I G ≤4.0.
[0023] According to some specific aspects of the present invention, I D / I GThe values include, but are not limited to, 2.5, 2.6, 2.7, 2.8, 2.85, 2.9, 2.95, 3.0, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30, 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.0, 4.1, 4.2, 4.3, and 4.5.
[0024] In this invention, I D / I G An increase in the value indicates an increase in the degree of disorder in the carbon structure of the catalyst, and an increase in the proportion of defective carbon and edge sites. Practice has proven that an appropriate amount of defective structure in the catalytic system of this invention is beneficial to increasing the exposure of active sites and improving the interfacial interaction between the metal active component and the conductive carbon support, thereby promoting the improvement of ORR catalytic performance.
[0025] In some embodiments of the present invention, the catalyst is prepared by a preparation method that satisfies the following conditions: (i) A transition metal precursor and a nitrogen precursor are used as raw materials, respectively. The transition metal precursor contains oxygen and the nitrogen precursor contains carbon. The transition metal precursor and the nitrogen precursor refer to substances that can be converted into the transition metal nitrogen coordination structure, the carbon-nitrogen compound, and the transition metal oxide through one or more conversion processes, respectively. (ii) Perform at least a portion of the one-step or multi-step conversion process in the presence of the conductive carbon.
[0026] In some embodiments of the present invention, the method for preparing the catalyst also satisfies the condition: (iii) the conversion treatment includes ball milling and heat treatment performed sequentially.
[0027] In this invention, ball milling can make the transition metal precursor and nitrogen precursor fully contact and uniformly dispersed through mechanical force. Then, heat treatment (preferably at a relatively low temperature) is used to form a nitrogen defect structure, which means that at least some of the structures in the metal-nitrogen coordination structure have unsaturated coordination characteristics. This constructs an active site system with metal-nitrogen coordination structure and nitrogen defect-related structure as the main components. At the same time, under the heat treatment conditions, the transition metal can also form transition metal oxides, and nitrogen can also form carbon and nitrogen compounds, which together regulate and enhance ORR activity.
[0028] In some embodiments of the present invention, the transition metal precursor is one or more combinations selected from the following: oxoacid salts of transition metals or their hydrates, basic hydroxides of transition metals or their partially dehydrated intermediates, and halide salt hydrates of transition metals.
[0029] In some embodiments of the invention, the transition metal precursor comprises a cobalt precursor and optionally a nickel precursor.
[0030] Further, the cobalt precursor comprises one or more combinations selected from cobalt hydroxide, cobalt hydroxyoxide, cobalt nitrate or its hydrate, cobalt carbonate or its hydrate, cobalt chloride hydrate, cobalt oxide or its hydrate, cobalt oxalate or its hydrate, and cobalt acetate or its hydrate; and the nickel precursor comprises one or more combinations selected from nickel hydroxide, nickel hydroxyoxide, nickel nitrate or its hydrate, nickel carbonate or its hydrate, nickel chloride hydrate, nickel oxide or its hydrate, nickel oxalate or its hydrate, and nickel acetate or its hydrate.
[0031] In some embodiments of the present invention, the nitrogen precursor includes melamine or a derivative thereof.
[0032] In some embodiments of the present invention, the nitrogen precursor includes one or more combinations selected from cyanamide, dicyandiamide, urea, polycyanamide polymers, pyrrole, and pyridine.
[0033] In some embodiments of the present invention, the conductive carbon includes one or more combinations selected from acetylene black, carbon black, Ketjen black, carbon nanotubes, and porous carbon.
[0034] According to some specific aspects of the invention, the porous carbon includes activated carbon and other carbons having a porous form.
[0035] In some embodiments of the present invention, the total amount of the transition metal precursor and the nitrogen precursor fed to the mass ratio of the conductive carbon fed is 1:0.1-10.0, further 1:0.5-5.0, even further 1:0.5-2.0, and still further 1:0.8-1.2.
[0036] According to some specific aspects of the present invention, the total feed ratio of the transition metal precursor and the nitrogen precursor to the feed mass ratio of the conductive carbon is 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5, 1:4.0, 1:4.5, 1:5.0, etc.
[0037] In some embodiments of the present invention, the molar ratio of the transition metal in the transition metal precursor to the nitrogen in the nitrogen precursor is 1:5-25, further 1:8-18, and even further 1:10-15.
[0038] According to some specific aspects of the present invention, the molar ratio of the transition metal in the transition metal precursor to the nitrogen in the nitrogen precursor is 1:5, 1:6, 1:7, 1:8, 1:9, 1:9.5, 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, etc.
[0039] This invention, through research on non-precious metal ORR catalysts and their preparation processes, proposes a catalyst preparation method combining ball milling pretreatment and low-temperature heat treatment. This method promotes sufficient contact between the transition metal precursor, nitrogen precursor, and carbon support, enabling the formation of metal-nitrogen related structures, metal-oxygen structures, and nitrogen-containing carbon structures during heat treatment, which collectively constitute the ORR active environment. In particular, in the Co-based catalyst system, introducing an appropriate amount of Ni component is beneficial for regulating the Co-related active structure, thereby further improving ORR catalytic performance. This invention can obtain catalysts with superior ORR performance at relatively low heat treatment temperatures, and has high preparation efficiency and potential for large-scale application.
[0040] Based on this, another technical solution provided by the present invention is: a method for preparing the above-mentioned catalyst for an air positive electrode, the preparation method comprising: (1) The transition metal precursor and the carbon-containing nitrogen precursor are mixed and ball-milled in a ball mill to obtain the first precursor; (2) The first precursor and conductive carbon are mixed and ball-milled in a ball milling device to obtain the second precursor; (3) The second precursor is calcined in a protective gas atmosphere, and the temperature of the calcination is controlled to be less than or equal to 700°C.
[0041] In this invention, the conductive carbon and the first precursor undergo a ball milling process together during the mixed ball milling, which is beneficial for their uniform dispersion throughout the system and for achieving mechanical activation treatment.
[0042] In some embodiments of the present invention, in step (3), the temperature of the calcination treatment is controlled to be 300-700°C, further to 450-650°C, and even further to 500-600°C.
[0043] According to some specific aspects of the present invention, in step (3), the temperature of the calcination treatment is controlled to be 300℃, 400℃, 420℃, 450℃, 480℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 600℃, 620℃, 650℃, 680℃, 700℃, etc.
[0044] In some embodiments of the present invention, in step (3), the heating rate of the calcination treatment is controlled to be 1-10℃ / min, and further to be 2-6℃ / min.
[0045] According to some specific aspects of the present invention, in step (3), the heating rate of the calcination treatment is controlled to be 1.0℃ / min, 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min, 4.0℃ / min, 4.5℃ / min, 5.0℃ / min, 5.5℃ / min, 6.0℃ / min, 6.5℃ / min, 7.0℃ / min, etc.
[0046] In some embodiments of the present invention, in step (3), the holding time of the calcination treatment is controlled to be 1-8h, and further to 2-5h.
[0047] According to some specific aspects of the present invention, in step (3), the holding time of the calcination treatment is controlled to be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.
[0048] In some embodiments of the present invention, in steps (1) and (2), the mixing ball mill is controlled to be carried out at a speed of 100-1000 rpm.
[0049] According to some specific aspects of the present invention, in steps (1) and (2), the mixing ball milling is controlled to be carried out at a rotational speed of 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm or 1000 rpm.
[0050] In some embodiments of the present invention, in steps (1) and (2), the mass ratio of the ball milling sample to the ball milling medium is controlled to be 1:10-80, and further to be 1:20-50.
[0051] According to some specific aspects of the present invention, in steps (1) and (2), the mass ratio of the ball milling sample to the ball milling medium is controlled to be 1:10, 1:20, 1:30, 1:35, 1:40, 1:45, 1:50, etc.
[0052] In some embodiments of the present invention, in step (1), the ball milling time of the mixed ball mill is controlled to be 5-72h, and further to 10-40h.
[0053] According to some specific aspects of the present invention, in step (1), the ball milling time of the mixed ball mill is controlled to be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 22h, 25h, 28h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 72h, etc.
[0054] In some embodiments of the present invention, in step (2), the ball milling time of the mixed ball mill is controlled to be 0.5-12h, and further to be 2-6h.
[0055] According to some specific aspects of the present invention, in step (2), the ball milling time of the mixed ball mill is controlled to be 0.5h, 0.8h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 10h, etc.
[0056] Another technical solution provided by the present invention is an air positive electrode, wherein the air positive electrode comprises the above-described air positive electrode catalyst, or comprises an air positive electrode catalyst prepared by the above-described preparation method.
[0057] Another technical solution provided by the present invention is a metal-air battery, wherein the metal-air battery includes the above-described air positive electrode.
[0058] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: Addressing the problems of complex preparation processes, high energy consumption, and insufficient catalytic performance of existing carbon-supported non-noble metal transition metal catalysts used in metal-air battery cathodes, the inventors of this invention have conducted in-depth research on non-noble metal ORR catalysts, such as carbon-supported non-noble metal transition metals, and their preparation processes. Breaking through the common understanding of those skilled in the art, they innovatively load nitrogen in carbon-supported non-noble metal transition metal catalysts in a manner that minimizes nitrogen doping within the carbon lattice. This differs from the common nitrogen-doped carbon structure; instead, the active site system is primarily constructed with transition metal-nitrogen coordination structures and nitrogen defect-related structures, and the transition metal oxide structure jointly regulates ORR activity. This not only results in ORR catalysts with superior ORR catalytic activity but also allows for preparation at relatively low temperatures. Furthermore, the method of this invention achieves high catalyst yields while maintaining excellent ORR catalytic activity, which helps reduce overall costs and is suitable for industrial applications. Attached Figure Description
[0059] Figure 1 The images shown are SEM images and EDX spectra of the material before calcination of the second precursor in Example 1. Figure 2 The images shown are SEM images and EDX spectra of the material after calcination of the second precursor in Example 1. Figure 3 TEM image (scale bar is 20 nm) of the air cathode catalyst prepared in Example 1. Figure 4 The images show the Raman scattering spectra of the materials before and after calcination of the second precursor in Example 1. Figure 5 The images show the XRD patterns of the materials before and after calcination of the second precursor in Example 1. Figure 6 The image shows the X-ray photoelectron spectroscopy (XPS) N 1s spectra of the materials before and after calcination of the second precursor in Example 1. Figure 7 The X-ray photoelectron spectroscopy (XPS) O 1s spectra of the materials before and after calcination of the second precursor in Example 1; Figure 8 The graph shows the linear sweep voltammetry test results of the air cathode catalysts obtained in Examples 1-5 of this invention. Figure 9 The graph shows the linear sweep voltammetry test results of the air cathode catalysts obtained in Examples 8-11 of this invention. Figure 10 The graph shows the linear sweep voltammetry test results of the air cathode catalysts obtained in Examples 6, 7, 17 and 18 of this invention. Detailed Implementation
[0060] The above-mentioned solution will be further described below with reference to specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0061] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0062] Example 1: This example provides a method for preparing an air positive electrode catalyst and the resulting air positive electrode catalyst. The preparation method includes: (1) Cobalt hydroxide and nickel hydroxide were added to the ball mill jar in a molar ratio of 1:1 between cobalt and nickel. Then, melamine was added to the ball mill jar in a molar ratio of 1:12.3 between the total molar amount of cobalt and nickel and the molar amount of nitrogen. Agate grinding balls were used as the grinding medium. The mass ratio of the material to be ground to the agate grinding balls was 1:34. The mixture was ball-milled at 400 rpm for 24 h to obtain the first precursor. (2) According to the first precursor and conductive carbon Super P (commercial conductive carbon black, BET is 62 m) 2 Conductive carbon Super P was added to the first precursor at a mass ratio of 1:1 (with an average secondary particle size of about 150 nm) and ball-milled at 400 rpm for 4 hours in a ball mill to obtain the second precursor. (3) The second precursor is transferred to a tube furnace and heated to 550°C at a rate of 3°C / min under a flowing nitrogen atmosphere. The temperature is maintained for 3 hours and then cooled to room temperature. The product is collected directly, which is the catalyst for the air cathode.
[0063] Example 2: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), the molar ratio of cobalt to nickel is 3:1.
[0064] Example 3: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), the molar ratio of cobalt to nickel is 1:0.
[0065] Example 4: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), the molar ratio of cobalt to nickel is 1:3.
[0066] Example 5: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), the molar ratio of cobalt to nickel is 0:1.
[0067] Example 6: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (2), the mass ratio of the first precursor to conductive carbon Super P is 2:3.
[0068] Example 7: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (2), the mass ratio of the first precursor to conductive carbon Super P is 2:1.
[0069] Example 8: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (3), the temperature is raised to 400°C.
[0070] Example 9: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (3), the temperature is raised to 700°C.
[0071] Example 10: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in steps (1) and (2), ball milling is not performed, but manual grinding and mixing is used instead.
[0072] Example 11: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that step (3) is omitted and the second precursor is directly used as the final air positive electrode catalyst.
[0073] Example 12: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that the temperature for heat preservation in step (3) is 300°C.
[0074] Example 13: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that the temperature for heat preservation in step (3) is 500°C.
[0075] Example 14: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), melamine is replaced with dicyandiamide according to the amount of nitrogen element with equimolar amounts.
[0076] Example 15: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), melamine is replaced with pyridine according to the amount of nitrogen element with equimolar amounts.
[0077] Example 16: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), cobalt hydroxide is replaced with an equimolar amount of cobalt nitrate and nickel hydroxide is replaced with an equimolar amount of nickel nitrate.
[0078] Example 17: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), melamine is added to the ball mill jar in a ratio of 1:24.6 of the total molar amount of cobalt and nickel to the molar amount of nitrogen.
[0079] Example 18: This example provides a method for preparing an air positive electrode catalyst and the air positive electrode catalyst prepared therefrom, which is basically the same as in Example 1, except that in step (1), melamine is added to the ball mill jar in a ratio of 1:9.225 of the total molar amount of cobalt and nickel to the molar amount of nitrogen.
[0080] Performance testing: (1) The materials before and after calcination of the second precursor in Example 1 were characterized, see [reference]. Figure 1 and Figure 2 As shown, Figure 1 The images show the SEM and EDX spectra before calcination. It can be seen that the material before sintering consists of primary nanoparticles. The EDX spectra show that the sample is composed of elements such as Co, Ni, N, and O, and they are evenly distributed, indicating that the precursor can be uniformly mixed after ball milling. Figure 2The SEM and EDX spectra after calcination show that the calcined material still exhibits a high nitrogen content, indicating that less nitrogen escapes during the calcination process and is largely retained in the sample. Meanwhile, calculations show that the nitrogen content of the second precursor before sintering is approximately 19.6 wt%, and the nitrogen content after sintering is approximately 18.4 wt%.
[0081] (2) Figure 3 The TEM image (scale bar is 20 nm) of the air cathode catalyst prepared in Example 1 shows that the materials in this invention have good contact and composite distribution, indicating that ball milling promotes uniform mixing and interfacial contact between different components, which provides a basis for the active structure in the subsequent low-temperature heat treatment process.
[0082] (3) Raman scattering spectroscopy analysis was performed on the materials before and after calcination of the second precursor in Example 1 using a laser with a wavelength of 532 nm to obtain... Figure 4 Raman test results show that: Before calcination, the precursors were Co(OH)₂ and Ni(OH)₂, with D and G peaks corresponding to characteristic carbon peaks, and C=N originating from the nitrogen source melamine. The calcination heat treatment caused changes in the cobalt-oxygen coordination environment and the degree of carbon defects, resulting in partial decomposition of the product into Co / Ni-O. The presence of the C=N peak indicates that some organic nitrogen was retained. D / I G The increase from 2.42 before calcination to 3.5 after calcination indicates that the disorder and defect level of the carbon structure increased after calcination. This suggests that heat treatment induced more defective carbon / edge sites, which is beneficial to improving the contact and exposure between the metal sites and the conductive carbon support.
[0083] (4) XRD characterization was performed on the materials before and after calcination of the second precursor in Example 1 (test conditions: phase analysis of the sample was performed using an X-ray diffractometer, and Cu Kα rays (λ=1.5406 Å) were used for the test, with a scanning range of 2θ=5°–90° and a scanning step size of 0.02°), and the results were obtained. Figure 5 XRD results showed that the second precursor before heat treatment mainly consisted of cobalt hydroxide, nickel hydroxide, and melamine. After heat treatment, the system underwent significant reconstruction, with the original hydroxide phase essentially disappearing, and the calcined product (catalyst for the air cathode) mainly consisting of Co2N. 0.67 C3N4, CoO, NiO.
[0084] (5) X-ray photoelectron spectroscopy (XPS) analysis was performed on the materials before and after calcination of the second precursor in Example 1. Figure 6Corresponding to the N 1s diagram, it can be seen that before calcination, CN=C, C=N, and C-NH2 correspond to the structures of melamine or its nitrogen-containing organic precursors; after calcination, Co / Ni-N, N-(C)3, and CNH appear, indicating that the nitrogen-containing precursors undergo condensation, cracking, and reconstruction: some nitrogen may form a metal-nitrogen coordination structure with Co / Ni; some form a graphite-like nitrogen / tri-coordinate nitrogen structure, i.e., N-(C)3; and some exist as residual CNH or incompletely condensed nitrogen-containing structures. Figure 7 Corresponding to the O 1s plot, it can be seen that before calcination, C=O corresponds to carbonyl groups on the surface of carbon materials, carbon oxide functional groups, or carbonyl structures in organic residues; after calcination, Co / Ni-OH is converted to Co / Ni-O. Heat treatment causes dehydration / reconstruction of metal hydroxides, forming metal oxides or metal-oxygen coordination environments. This corresponds to the presence of CoO and NiO in XRD and the presence of 500 cm⁻¹ in Raman spectroscopy. -1 The nearby cobalt-related oxygen-containing vibrations are matched.
[0085] (6) The yield of the catalyst used in the preparation process of the air cathode in Example 1 was 64.7%, and the yield of Example 9, which was sintered at a higher temperature, was 43.7%. It can be seen that in the catalytic system of the present invention, a lower sintering temperature is beneficial to obtaining a catalyst product with a high yield. In other words, the present invention can reduce production costs to a certain extent. The yield is calculated as: mass after sintering / mass before sintering.
[0086] (7) Linear scan voltammetry was performed on the air cathode catalysts obtained in Examples 1-11 and 17-18. The test method was as follows: the catalyst was prepared into a catalytic ink and drop-coated onto the surface of a glassy carbon electrode. In an O2-saturated 1 M KOH electrolyte, a rotating disk electrode (1600 rpm) was used to perform linear scan voltammetry at a scan rate of 5 mV / s. The test results are shown in Table 1 and Figure 8-10 As shown; In the table, E onset The onset potential (in V) is the potential at which the current begins to deviate significantly from the baseline (or reaches a specific low current density), and is typically used to characterize the critical point at which a catalyst begins to react; E onset The larger the absolute value, the higher the initial activity.
[0087] E 1 / 2 Half-wave potential (unit: V) is the potential corresponding to half of the limiting diffusion current, and is commonly used to comprehensively evaluate the ORR kinetic activity of a catalyst; E 1 / 2 The more positive the value, the better the overall ORR catalytic activity of the catalyst under the same test conditions.
[0088] j L Limiting current density (unit mA·cm)-2 The current density (DC) is the maximum current density achievable in an electrochemical reaction under mass transfer (diffusion) control. It is typically used to evaluate the current response capability of a catalyst under mass transfer-constrained conditions. L The larger the value, the higher the diffusion-limiting current response and the better the mass transfer-related performance of the catalyst.
[0089] Table 1 Electrochemical test results show that: 1. Co-based catalysts alone have shown high ORR activity, while Ni-based catalysts alone have relatively low overall activity. Introducing an appropriate amount of Ni improves the onset potential, half-wave potential, and limiting current density of the Co-Ni synergistic catalyst, with the sample exhibiting the best performance when the Co:Ni ratio is 1:1. Analysis suggests that in the catalyst system of this invention, Ni does not act as the primary ORR active center, but rather, at an appropriate ratio, it regulates and stabilizes the electronic structure of Co-related active sites, thereby enhancing the overall ORR catalytic performance.
[0090] 2. Meanwhile, the calcination temperature of about 550℃ is relatively optimal. The calcination temperature of this invention can cause the coordination between some transition metals and nitrogen to break, forming nitrogen defects. However, this temperature is relatively low and is not intended to promote the entry of N doping into the carbon framework. It can be seen that this invention obtains an air cathode catalyst with good electrochemical performance under relatively low preparation energy consumption conditions, which is conducive to large-scale industrial production.
[0091] 3. A comparison of Examples 1 and 10 shows that ball milling is more conducive to improving the catalytic performance of the catalyst. The half-wave potential and the onset potential are significantly increased, and the limiting current density is increased by about 23.9%. The improvement in ORR electrochemical performance is unexpected. Further analysis suggests that this may be because, in the catalytic system of the present invention, the ball milling process does not only play a simple physical mixing role, but may also promote the interfacial interaction between precursors through mechanical activation, which is beneficial to the formation of specific structures with high activity at relatively low temperatures.
[0092] As used throughout the specification and claims, the term "comprising" is an open-ended term and should be interpreted as "comprising but not limited to." "Substantially" means that within an acceptable margin of error, those skilled in the art can solve the technical problem and substantially achieve the technical effect. It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a product or system comprising a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a product or system. Without further limitations, an element defined by the phrase "comprising one" does not exclude the presence of other identical elements in the product or system comprising said element.
[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0094] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A catalyst for an air positive electrode, characterized in that, The catalyst comprises conductive carbon, a transition metal, and nitrogen; some nitrogen exists in the form of a metal-nitrogen coordination structure with the transition metal, wherein at least part of the metal-nitrogen coordination structure has a transition metal center with an actual coordination number less than the theoretical coordination number, and some nitrogen exists in the form of carbon-nitrogen compounds, and the transition metal also exists in the form of transition metal oxides.
2. The catalyst for an air positive electrode according to claim 1, characterized in that, The transition metal includes at least cobalt, and the metal nitrogen coordination structure includes CoN. 4-x x is greater than or equal to 0 and less than 4; and / or, The transition metal comprises cobalt and nickel, wherein the molar ratio of cobalt to nickel is 1:0-5.0, more preferably 1:0.1-2.0, and even more preferably 1:0.5-1.5; and / or, The carbon-nitrogen compounds include carbon nitrides, and further include carbon-nitrogen-hydrogen compounds; and / or, The transition metal oxide comprises at least cobalt oxide, and further comprises nickel oxide; and / or, The molar ratio of the transition metal to the nitrogen is 1:5-25, more preferably 1:8-18, and even more preferably 1:10-15; and / or, When the catalyst was analyzed by Raman scattering spectroscopy using a laser with a wavelength of 532 nm, the Raman shift was 1330-1360 cm⁻¹. -1 The D peak intensity is I D The Raman shift is 1570-1600 cm. -1 The intensity of the G peak is I G 2.5≤I D / I G Furthermore, 2.5≤I D / I G ≤5.0, and further, 2.8≤I D / I G ≤4.
0.
3. The catalyst for an air positive electrode according to claim 1, characterized in that, The catalyst is prepared by a method that satisfies the following conditions: (i) A transition metal precursor and a nitrogen precursor are used as raw materials, respectively. The transition metal precursor contains oxygen and the nitrogen precursor contains carbon. The transition metal precursor and the nitrogen precursor refer to substances that can be converted into the transition metal nitrogen coordination structure, the carbon-nitrogen compound, and the transition metal oxide through one or more conversion processes, respectively. (ii) Perform at least a portion of the one-step or multi-step conversion process in the presence of the conductive carbon.
4. The catalyst for an air positive electrode according to claim 3, characterized in that, The preparation method of the catalyst also satisfies the condition: (iii) the conversion treatment includes ball milling and heat treatment performed sequentially.
5. The catalyst for an air positive electrode according to claim 3, characterized in that, The transition metal precursor is one or more combinations selected from oxoacid salts or hydrates of transition metals, basic hydroxides of transition metals or their partially dehydrated intermediates, and halide hydrates of transition metals; further, the transition metal precursor includes a cobalt precursor and optionally a nickel precursor; more further, the cobalt precursor includes one or more combinations selected from cobalt hydroxide, cobalt hydroxyoxide, cobalt nitrate or its hydrate, cobalt carbonate or its hydrate, cobalt chloride hydrate, cobalt oxide or its hydrate, cobalt oxalate or its hydrate, and cobalt acetate or its hydrate; the nickel precursor includes one or more combinations selected from nickel hydroxide, nickel hydroxyoxide, nickel nitrate or its hydrate, nickel carbonate or its hydrate, nickel chloride hydrate, nickel oxide or its hydrate, nickel oxalate or its hydrate, and nickel acetate or its hydrate; and / or, The nitrogen precursor includes one or more combinations selected from cyanamide, dicyandiamide, urea, melamine polymers, pyrrole, and pyridine; further, the nitrogen precursor includes melamine or a derivative thereof.
6. The catalyst for an air positive electrode according to claim 3, characterized in that, The conductive carbon comprises one or more combinations selected from acetylene black, carbon black, Ketjen black, carbon nanotubes, and porous carbon; and / or, the total feed ratio of the transition metal precursor and the nitrogen precursor to the conductive carbon is 1:0.1-10, further 1:0.5-5, even further 1:0.5-2.0, and still further 1:0.8-1.2; and / or, the molar ratio of the transition metal element in the precursor to the nitrogen element in the precursor is 1:5-25, further 1:8-18, and even further 1:10-15.
7. A method for preparing a catalyst for an air cathode according to any one of claims 1-6, characterized in that, The preparation method includes: (1) The transition metal precursor and the carbon-containing nitrogen precursor are mixed and ball-milled in a ball mill to obtain the first precursor; (2) The first precursor and conductive carbon are mixed and ball-milled in a ball milling device to obtain the second precursor; (3) The second precursor is calcined in a protective gas atmosphere, and the temperature of the calcination is controlled to be less than or equal to 700°C.
8. The preparation method according to claim 7, characterized in that, In step (3), the temperature of the calcination treatment is controlled to be 300-700℃, further to 450-650℃, and even further to 500-600℃; and / or, in step (3), the heating rate of the calcination treatment is controlled to be 1-10℃ / min, further to 2-6℃ / min; and / or, in step (3), the holding time of the calcination treatment is controlled to be 1-8h, further to 2-5h; and / or, in steps (1) and (2), the temperature of the calcination treatment is controlled to be 300-700℃, further to 450-650℃, and even further to 500-600℃; and / or, in steps (1) and (2), the temperature ...300-700℃, further to 450-650℃, and even further to 500-600℃; and / or, in steps (1) and (2), the temperature of the calcination treatment is controlled to be 1-10℃ / min, further to 2-6℃ / min; and / or, in steps (3), the holding time of the calcination treatment is controlled to be 1-8h, further to 2-5h; and / or, in steps (1) and (2), the temperature of the calcination treatment is controlled to be 3 The ball milling is carried out at a speed of 100-1000 rpm; and / or, in steps (1) and (2), the mass ratio of the ball milling sample to the ball milling medium is controlled to be 1:10-80, and further to 1:20-50; and / or, in step (1), the ball milling time is controlled to be 5-72h, and further to 10-40h; and / or, in step (2), the ball milling time is controlled to be 0.5-12h, and further to 2-6h.
9. An air positive electrode, characterized in that, The air positive electrode comprises an air positive electrode catalyst according to any one of claims 1-6, or comprises an air positive electrode catalyst prepared by the preparation method according to claim 7 or 8.
10. A metal-air battery, characterized in that, The metal-air battery comprises the air positive electrode as described in claim 9.
Citation Information
Patent Citations
A nano-nickel-iron nitride composite material supported on a cobalt-nitrogen co-doped nitrogen-carbon material carrier, its preparation method and application.
CN106887576B
Preparation method and application of an iron / copper nitrogen-doped graphene zinc-air battery cathode catalyst
CN110247068B
Preparation and application of nitrogen-doped carbon nanotube-supported nickel-cobalt composite nanowires
CN114744224B
Graphene-loaded nickel-cobalt diatomic catalyst, preparation method thereof and lithium air battery
CN119890554A